Persistent Production Gaps Due to Input Bottlenecks - Hubertus Bardt; Michael Grömling (Wirtschaftsdienst)
Abstract Ongoing problems with the procurement of intermediates are weighing on the German economy. Three-quarters of companies are currently reporting production losses averaging 7%. The situation will not improve significantly until the second half of 2022. But even in 2023, just under half of private-sector companies still expect shortfalls. In addition to the lack of intermediates, the shortage of skilled workers is a permanent brake on production.